2015
DOI: 10.1002/pd.4606
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Down syndrome risk according to maternal age: “1-in-X ” effect on perceived risk

Abstract: The present findings corroborate the existence of the 1-in-X effect in a real-world setting, showing that, in pregnant women, the 1-in-X format actually elicits a higher perceived risk of Down syndrome, compared with the N-in-NX format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The expected age-specific rate in each age group was calculated according to the selected model. All rates in this study were reported in the format of “number of cases per 1,000” as previously recommended [3]. …”
Section: Methodsmentioning
confidence: 99%
“…The expected age-specific rate in each age group was calculated according to the selected model. All rates in this study were reported in the format of “number of cases per 1,000” as previously recommended [3]. …”
Section: Methodsmentioning
confidence: 99%
“…A common format for risks is "1 in X," which the preceding argument suggests should tend to make risks look smaller than, say, "10 out of 10X." This format has been strongly criticized (Zikmund-Fisher 2014), although a recent review argued that this effect is smaller than claimed (Sirota et al 2014), and a recent study found that "1 in X " can even be seen as suggesting higher risks than when expressed with a higher numerator (Pighin et al 2015), particularly for participants with low educational level. Table 1 illustrates a range of comparative measures applied to the example described in the sidebar Is Bacon as Dangerous as Cigarettes?…”
Section: Chances As Fractionsmentioning
confidence: 99%
“…In addition, a recent study showed that 80% of the participating UK family physicians systematically preferred to communicate prenatal risk using ‘1‐in‐X’ ratios . However, pregnant women who received Down syndrome risk information using this information format perceived that they are at higher risk compared with women who received the same information as a proportion of 1000 . Overall, there is decisive evidence that 1‐in‐X ratios lead to greater perceived probability and worry, compared with other formats such as percentages or ratios out of 100, which tend to result in more homogeneous perceptions .…”
Section: Avoid Using the 1‐in‐x Format To Describe The Riskmentioning
confidence: 83%
“…This suggests that a substantial proportion of women will not be able to make sense of risk communications about Down syndrome. For instance, after receiving information about the risk of having a child with Down syndrome, only 30–40% of women correctly indicated their chances of not having a child with Down syndrome . In addition, patients (and even medical professionals) have serious difficulties inferring the positive predictive value of tests from information about the prevalence of a disease and the sensitivity and false‐positive rate of the test .…”
Section: Why Is Careful Risk Communication Needed?mentioning
confidence: 99%